Effect on Balance According to Various Recovery Techniques after Induce Muscle Fatigue in Male College Students - Minkyo Kim; Hyun-Joo Kang (Asian Society of Kinesiology, 2024)
OBJECTIVES The purpose of this study was to effect balance according to various recovery techniques after Harvard step test-induced muscle fatigue in male college students. METHODS Twenty male college students(22.20±2.06 yrs, 177.80±4.28 cm, 77.50±4.28 kg) participated in the study, and their static balance and dynamic balance(Humac balance system) were measured after inducing lower extremity muscular fatigue using Harvard step test. Muscle fatigue was treated in the following order: no treatment in the 1st week, stretching in the 2nd week, icing therapy in the 3rd week, and sports massage in the 4th week, and then post-test was performed in the same manner as the pre-test. RESULTS In the case of static balance, path length on eye opened-foam was a significant difference in interaction effect between the group and time(p<0.001). Also, average velocity on eye opened-foam was a significant difference in interaction effect between the group and time(p<0.001). Dynamic balance was no a significant difference to recovery techniques(stretching, icing therapy, and sports massage). CONCLUSIONS Various recovery techniques such as stretching, icing, and sports massage after the Harvard step test-induced muscle fatigue in male college students did not affect balance. In future research, it is crucial to enhance the scope of the target group, various methods of inducing muscle fatigue, and identify the effects of recovery techniques.